1975
DOI: 10.1002/pol.1975.170130217
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric investigation of polymerization reactions. V. Crosslinked copolymerization of methyl methacrylate with ethylene dimethacrylate

Abstract: The crosslinked copolymerization of methyl methacrylate with ethylene dimethacrylate (EDMA) in bulk and in toluene has been investigated by differential scanning calorimetry. The appearance of a second peak, in addition to that arising from the gel effect, noted in curves of bulk copolymerization rate (fraction of EDMA mE = 0.20) is explained by the formation of microgels during the copolymerization. With mE = 0.50–1.00, copolymerization proceeds heterogeneously at first, providing opaque microgels, which beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 14 publications
3
77
1
Order By: Relevance
“…Previous investigations have also reported a bimodal rate of polymerization for the methacrylate system (Horie et al 1975;Anseth et al 1994;Yu et al 2001). Horie et al (1975) suggested that there could be an accumulation of pendant double bonds during polymerization due to their reactivity being lower than the free monomers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations have also reported a bimodal rate of polymerization for the methacrylate system (Horie et al 1975;Anseth et al 1994;Yu et al 2001). Horie et al (1975) suggested that there could be an accumulation of pendant double bonds during polymerization due to their reactivity being lower than the free monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Horie et al (1975) suggested that there could be an accumulation of pendant double bonds during polymerization due to their reactivity being lower than the free monomers. During later stage of the polymerization, these pendant double bonds could form higher cross-linked regions called microgels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing cross-links into a latex film can increase its physical and chemical stability as well as improve its tensile strength and abrasion resistance [65]. As a consequence, there is a deep and growing interest within the coating industry in cross-linked water-borne coatings.…”
Section: Cross-linkersmentioning
confidence: 99%
“…Ethylene glycol dimethacrylate (EGDM) has been widely used as a cross-linking agent in the synthesis of hydrophilic or hydrophobic co-polymer networks [55]. Some aspects of the co-polymerization of MMA with EGDM have been investigated since 1945 [14,[56][57][58][59][60][61][62][63][64][65][66]. Some authors estimated the efficiency of cross-linking [57,63] or determined the glass transition temperature of the co-polymer [58] (Table 3).…”
Section: Cross-linkersmentioning
confidence: 99%